Directive Speech Act Found in Renee Carlino “Swear on This Life” - Agnes Novalia; Robby Satria (LPPM Universitas Bumigora Mataram, 2023)
Directive speech acts are regularly used in daily basis conversation between human. This study used descriptive qualitative studies to discover the types of directive speech acts in Renee Carlino’s “Swear on This Life”. Data collection utilized observational non-participatory technique that took utterances found in the novel. The utterances are analyzed using Searle & Vanderveken (1985) theory of illocutionary acts. The data utilized pragmatic identity method along with pragmatic competence as a comparison to Sudaryanto, (2015). The conclusion of this study proved that there are 20 utterances indicating directive speech acts found in Renee Carlino’s “Swear on This life”. There are 5 data showing requesting, 3 data showing ordering, 6 data showing forbidding, 3 data showing warning, 3 data showing permitting. Forbidding is shown as the most frequently found as the characters have different opinion on each other’s action.